Catalytic stability of a Ni-Catalyst towards biogas reforming in the presence of deactivating trace compounds. (November 2018) - Papurello, Davide; Chiodo, Vitaliano; Maisano, Susanna; Lanzini, Andrea; Santarelli, Massimo
Abstract: Trace compounds contained in the produced biogas range from tens to thousands of ppm(v) and the gas cleaning is crucial, as much as it is important the investigation of the trace compounds impact on the reforming section and on the SOFC performance. The catalytic stability of a Ni-catalyst towards biogas reforming in the presence of three types of deactivating compounds (sulfur, siloxanes and aromatic compounds) was investigated. When the biogas is composed of a methane to carbon dioxide ratio >1 under the tested operating conditions, the Ni catalyst stability is achieved. A Ni/Al2 O3 catalyst appears suitable for the steam reforming of biogas including contaminants, under the operative conditions adopted. On the contrary, the effect of a biogas stream with composition CH4 /CO2 = 50/50 vol % is much more harmful under steam reforming conditions both in terms of activity and stability. This result was due to CO2 -promoted Boudouard reaction that leads to extensive carbon formation on the catalyst surface. Under this condition, sulfur and D5 compounds in the biogas have a significant impact on the longevity of the Ni catalyst. Hence, carbon formation rate is affected by the degree of catalyst poisoning due to adsorption and/or deposition of other species on catalytic sites. Highlights: Ni catalyst stability is achieved with biogas mixture with CH4/CO2>1. CH4/CO2 = 50/50 vol % is much more harmful under steam reforming conditions both in terms of activity and stability. The impact of trace contaminants not removed from the cleaning section from biogas are investigated on SOFCs.